2002
DOI: 10.1021/la011844e
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the Orientational Response of Liquid Crystals to Proteins Specifically Bound to Covalently Immobilized and Mechanically Sheared Films of Functionalized Bovine Serum Albumin

Abstract: This paper reports on the orientational behavior of thermotropic liquid crystals supported on films of biotinylated bovine serum albumin (BSA) that are covalently immobilized on the surface of glass substrates using (3-aminopropyl)triethoxysilane (APES) and disuccinimidyl suberate (DSS). The films of biotinylated BSA are mechanically sheared and then immersed into aqueous solutions of anti-biotin immunoglobulin G (IgG) prior to contact with nematic phases of 4-cyano-4′-pentylbiphenyl (5CB). Using ellipsometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
(24 reference statements)
0
27
1
Order By: Relevance
“…[2][3][4][12][13][14][15] Examples of recent progress include the use of LCs to report the presence of viruses captured at surfaces, [12] amplify receptor-ligand binding events involving proteins, [2] and report enzymatic activity. [3,13] Additionally, several studies have explored LCs as materials to create interfaces to mammalian cells. [4,15] Fang et al demonstrated that the thermotropic LC, 4-cyano-4 0 -pentylbiphenyl (5CB) assumed distinct orientations when it was layered over several different cell lines cultured on glass substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][12][13][14][15] Examples of recent progress include the use of LCs to report the presence of viruses captured at surfaces, [12] amplify receptor-ligand binding events involving proteins, [2] and report enzymatic activity. [3,13] Additionally, several studies have explored LCs as materials to create interfaces to mammalian cells. [4,15] Fang et al demonstrated that the thermotropic LC, 4-cyano-4 0 -pentylbiphenyl (5CB) assumed distinct orientations when it was layered over several different cell lines cultured on glass substrates.…”
mentioning
confidence: 99%
“…The observation that several micrometersized LC domains of the CLC were covered by each fibroblast cell suggests that it may be possible to exploit the reordering of the LCs within those domains to report biomolecular and/or mechanical interactions with the LC. Past studies have demonstrated that subtle interactions of LCs with proteins, [2,13] lipids, [3] or surfactants [26] can induce changes in the orientational order of the LCs. To determine if interfacial interactions can dictate the ordering of LCs within the LC-rich domains of CLC gels, we confined the CLCs between chemically functionalized glass microscope slides that give rise to known orientations of the LCs.…”
mentioning
confidence: 99%
“…The advantages of LC biosensors include high sensitivity, low cost, ease of use and their labelfree nature. Recent studies have shown that LCs can transduce and amplify the presence of proteins, phospholipids, DNA, cells and viruses into optical readouts visible to the naked eye [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…10,[12][13][14][15] These important characteristics of LC based biosensors make them well suited for simple detection, direct transduction, high sensitivity, and low-cost bioassays. [16][17][18][19] For the detection of enzymatic events, few LC biosensors have been reported because most of the enzymatic reactions catalyze substrate to generate some small-molecule products, whose disruption behaviour to the orientation of LC molecules is far smaller than that of macro-biomolecules. 13,[20][21][22] Recently, Liao and co-workers developed a LC biosensing system based on the enzymatic growth of gold nanoparticles (Au NPs) for the detection of acetylcholine (ACh) and acetylcholinesterase (AChE) inhibitor.…”
mentioning
confidence: 99%